SPAIN PORTUGAL 50 Geography Facts You Never Knew About The Iberian Peninsula (2026)
50 Geography Facts You Never Knew About The Iberian Peninsula Most people think the Iberian Peninsula is just Spain and Portugal. They're wrong. Europe's only true desert is here. A river so acidic it looks like it's from another planet. Mountain peaks that are actually submerged underwater. A strait where two currents flow in opposite directions simul